(untitled) - Kingsbury, Karen (Thorndike Press, 2007)
Living an ideal life with her devoted husband and two daughters, Hannah Ryan finds her faith tested when her husband and oldest daughter are killed by a drunken driver, and she must work her way through her grief and rage to learn forgiveness.
"Prequel to Moment of weakness"--T.p. verso.
Keywords: Large print books